From the Mouths of Mothers: Can Drama Facilitate Reflective Learning for Social Workers?. Issue 4 (18th May 2016) - Leonard, Kate; Gupta, Anna; Stuart Fisher, Amanda; Low, Katharine
Abstract: This article explores and evaluates a cross-disciplinary small-scale project using applied theatre in social work education. The aim was to provide an 'Affective Encounter' where students could practice empathic engagement, understanding of the needs of children who have been sexually abused and their protective parents/carers and engage in the complexities of working with family members who may be resistant. The workshop took place five times over a period of three years and was attended by children and families social workers on a one year post-qualifying graduate diploma course. While the use of verbatim theatre does not offer a guarantee of factual truth, it provided the students with some performed moments of personal testimony which was taken word-for-word from mothers whose children had been sexually abused. This allowed the social workers to hear the marginalised narratives of the protective mothers and to practice without a negative impact on the service user. The evaluation identified from self-report the development of emotional and practical skills and knowledge of available resources. This paper focuses on the emotional skills reported and two emerging themes are discussed: learning for humane practice, and the use of this pedagogical approach to encourage affective reflection.